Seroprevalensi Infeksi Toxoplasma gondii pada Babi di Lembah Baliem dan Pegunungan Arfak Papua - YOGA LOKANTARA, I PUTU; DAMRIYASA, I MADE; DWINATA, I MADE (Indonesia Medicus Veterinus, 2012)
This study aims to determine the presence of Toxoplasma gondii in pigs at the Baliem Valley and at the Mountains of Arfak Papua. Using the Indirect test Haemaglutination Asay, Primary Cellognost * Toxoplasmosis ? H (IHA reagent Toxoplasmosis), Reagent Buffer, Buffer Serum, Toxoplasmosis Control Serum, positive (IgG), Toxoplasmosis Control Serum, negative, and Pig Serum. The results showed the presence of Toxoplasma gondii in pigs at the Baliem Valley is (75.9%) and at the Mountains of Papua Arfak amounts (25%),